Demographic and Clinical Characteristics of Completed Suicides in Mexico City 2014–2015 - Romero-Pimentel, Ana L.; Mendoza-Morales, Roberto C.; Fresan, Ana; Garcia-Dolores, Fernando; Gonzalez-Saenz, Eli E.; Morales-Marin, Mirna E.; Nicolini, Humberto; Borges, Guilherme (Frontiers in Psychiatry, 2018)
Objective: To analyze sex differences in demographic and clinical characteristics of individuals who died by suicide in Mexico City Method: Statistical analysis of residents of Mexico City whose cause of death was suicide, from January 2014 to December 2015, with a coroner’s report. Suicide mortality rates were calculated by age, sex, and location within the city. The Chi-squared test was used to assess statistical differences. Results: From January 2014 to December 2015, 990 residents of Mexico City died by suicide (men: 78.28%, women: 21.72%). Among males, the highest mortality rates were among the groups of 20 to 24 and 75 to 79 years old, whereas in women, the group with the highest mortality rate was 15 to 19 years old. 74% of the sample used hanging as suicide method. However, men had higher rates of a positive result in the toxicology test (40%) (p <0.05). There was no concordance between male and female suicide by city jurisdictions. Conclusion: Our results provide evidence that the characteristics of Mexico City’s residents who committed suicide had significant sex-related differences, including where they used to live. Understanding the contributory factors associated with completed suicide is essential for the development of effective preventive strategies.